ROAD FREIGHT TRANSPORT ENTITIES DEALING WITH THE COVID-19 PANDEMIC - Cosmulese, Cristina Gabriela (Studies and Scientific Researches. Economics Edition, 2023)
The road transport business has changed dramatically in the previous three years and will confront new problems in the next years. From the start of the pandemic crisis to the current geopolitical and economic uncertainty, industry players have had to constantly come up with new ways to deal with the paradigm shift and support clients. The aim of this paper is to identify, through a comparative analysis of SMEs in the road transport sector, if and how they contribute to job creation and what economic contribution they make in Romania in the context of the pandemic crisis. For this purpose, through the topfirme.com platform, the economic and financial statements of a sample of 100 enterprises were collected for the period 2016-2020. The study suggests that small firms are significantly more willing than medium and big businesses to endure financial troubles and take remedial steps in this context. However, according to the analysis, the group of tiny firms manages to cope well with uncertainties and shifting market trends in the case of the current study, based on the indicators examined